Pendidikan Anti Bullying Persfektif Abdullah Nasih Ulwan - Sa'adah Erliani (Program Studi PGSD STKIP PGRI Banjarmasin, 2020)
Abstract: Many cases of violence that occur in schools. This needs special attention so that violence in educational institutions does not recur. Anti-bullying children's education perspective Abdullah Nasih Ulwan is a way for Islamic education experts to explain the concept of education without violence. This research is a library research, which is a literature study through library research by discussing anti-bullying education in the book